Political participation and quality of life - Rebecca Weitz-Shapiro; Matthew S. Winters (Inter-American Development Bank, Research Department, 2008)
Theoretical literatures on procedural utility and the psychological benefits of political participation suggest that people who participate in political activities will be more satisfied with their lives because of the resulting feelings of autonomy, competence and relatedness. Individual-level data from Latin America show - in one dataset under study but not in another - a positive and statistically significant relationship between voting and life satisfaction. Variation in desire to vote as measured in Costa Rica, however, suggests that the causal arrow may run from happiness to voting. The use of multilevel models further reveals a consistent - but untheorized - cross-country negative relationship between enforced compulsory voting and happiness. Only preliminary results are found regarding the relationship between some other forms of political participation and life satisfaction.
Keywords: 330